On the problem of singular limit - Caggio, Matteo (Matematický ústav, Žitná 25, 115 67 Praha 1, http://www.math.cas.cz, 2023)
We consider the problem of singular limit of the compressible Euler system confined to a straight layer Ωδ = (0, δ)×R², δ > 0. In the regime of low Mach number limit and reduction of dimension the convergence to the strong solution of the 2D incompressible Euler system is shown.
Keywords: dissipative measure-valued solutions; compressible Euler equations; low Mach number; thin domain